Summary of the political implications of my research - Madaha, Rasel (CLACSO, 2021)
Tanzania has desperately been addressing its developmental challenges by looking for solutions from elsewhere. It is as if Tanzania waits for a Messiah from a different world to come and rescue it from its development challenges. Tanzania and so are Tanzanians know that the current neoliberal development model is not in position to foster moral, spiritual, ethical and civil values embedded in national unity, social cohesion, peace and stability. This is the time for Tanzania to importune for another viable and sustainable development approach. It is argued here that Tanzania needs to come up with a context specific development approach which is free from frameworks of modernity such as socialism and neoliberalism and instead should take the local context into consideration.